Epicardial ventricular tachycardia in ischemic cardiomyopathy: Prevalence, electrophysiological characteristics, and long‐term ablation outcomes. (8th October 2018) - Hayashi, Tatsuya; Liang, Jackson J.; Muser, Daniele; Shirai, Yasuhiro; Enriquez, Andres; Garcia, Fermin C.; Supple, Gregory E.; Schaller, Robert D.; Frankel, David S.; Lin, David; Nazarian, Saman; Zado, Erica S.; et al.
Abstract: Introduction: The characteristics of the epicardial (EPI) substrate responsible for ventricular tachycardia (VT) in ischemic cardiomyopathy (ICM) are undefined, and data on the long‐term outcomes of EPI catheter ablation limited. We evaluated the prevalence, electrophysiologic features, and outcomes of catheter ablation of EPI VT in ICM. Methods and Results: From December 2010 to June 2013, a total of 13 of 93 (14%) patients with ICM underwent catheter ablation at our institution and had conclusive evidence of critical EPI substrate demonstrated to participate in VT with activation, entrainment and/or pace mapping during sinus rhythm (two other patients underwent EPI mapping but had no optimal ablation targets). The electrophysiologic substrate characteristics and activation/entrainment mapping data were compared with a reference group of ICM patients without evidence of critical EPI substrate ( N  = 44), defined as a complete procedural success (noninducibility of any VT at programmed stimulation) after endocardial (ENDO)‐only ablation. Patients with failed EPI access ( N  = 2) or history of cardiac surgery ( N  = 92) were excluded from the study. All 13 patients had evidence of abnormal EPI substrate with fractionated/late/split electrograms and low‐bipolar voltage areas. The critical VT ablation sites were all located within the EPI bipolar "dense" scar (<1.0 mV) opposite the ENDO bipolar scar in 77% of cases and extending beyond the ENDO bipolar scar (within the ENDO unipolar low‐voltage area) in the remaining patients. Compared with the reference ENDO‐only group, patients with EPI VT had a smaller ENDO bipolar scar area, 54.0 (37.1‐84) vs 86.7 (55.6‐112) cm 2 ; P  = 0.0159, with a similar extent of ENDO unipolar low voltage. No other substrate characteristics or location differed between the two groups. After 35.2 ± 24.2 months of follow‐up, VT‐free survival was 73% in patients with EPI VT compared with 66% in the ENDO‐only group (log‐rank P  = 0.56). Conclusions: The presence of the critical EPI substrate responsible for VT can be demonstrated in at least 14% of patients with ICM. The majority of EPI critical ablation sites are distributed opposite the ENDO bipolar scar area and catheter ablation is effective in achieving long‐term arrhythmia control.